2016
DOI: 10.1001/jamaoncol.2015.4701
|View full text |Cite
|
Sign up to set email alerts
|

Palbociclib (PD0332991)—a Selective and Potent Cyclin-Dependent Kinase Inhibitor

Abstract: Palbociclib is well tolerated and has therapeutic potential for multiple cancers, including breast cancer, where its efficacy has been demonstrated alone and in combination with endocrine therapy. Additional combinations of palbociclib with endocrine therapy, chemotherapy, and targeted therapy have potential in various tumors, and phase 3 trials are under way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(82 citation statements)
references
References 65 publications
3
76
0
3
Order By: Relevance
“…Currently, data on the genetic alterations in these rare tumours are lacking 56 . More specific and patient-targeted therapies are now becoming available for certain noncardiac sarcomas, including agents such as trabectedin (a DNA-damaging agent that specifically targets cells deficient in homologous recombination and immune modulatory properties), palbociclib (a cyclin-dependent kinase 4/6 inhibitor used in the treatment of liposarcomas), pazopanib (a multitargeted tyrosine kinase inhibitor against vascular endothelial growth factors used for nonliposarcomas), and olaratumab (a monoclonal antibody directed against platelet-derived growth factor-α for undifferentiated pleomorphic sarcoma and liposarcoma, in combination with doxorubicin) [57][58][59][60][61][62][63][64][65][66][67] . Whether any of these therapies will have a role in the treatment of cardiac sarcomas is unknown.…”
Section: Hamartoma Of Mature Cardiac Myocytesmentioning
confidence: 99%
“…Currently, data on the genetic alterations in these rare tumours are lacking 56 . More specific and patient-targeted therapies are now becoming available for certain noncardiac sarcomas, including agents such as trabectedin (a DNA-damaging agent that specifically targets cells deficient in homologous recombination and immune modulatory properties), palbociclib (a cyclin-dependent kinase 4/6 inhibitor used in the treatment of liposarcomas), pazopanib (a multitargeted tyrosine kinase inhibitor against vascular endothelial growth factors used for nonliposarcomas), and olaratumab (a monoclonal antibody directed against platelet-derived growth factor-α for undifferentiated pleomorphic sarcoma and liposarcoma, in combination with doxorubicin) [57][58][59][60][61][62][63][64][65][66][67] . Whether any of these therapies will have a role in the treatment of cardiac sarcomas is unknown.…”
Section: Hamartoma Of Mature Cardiac Myocytesmentioning
confidence: 99%
“…Palbociclib inhibits cell growth and DNA replication in a number of retinoblastoma (Rb) proficient human cancer cells, including breast cancer because over 70% of breast cancers are Rb proficient [70]. Palbociclib is a well-tolerated cancer therapeutic [71] that induces G0/G1 arrest in HER2/neu− and HER2/neu+ breast tumor cells [69,72] as well as in neu positive murine mammary tumor cells [73]. Palbociclib can be administered at a concentration of 150 mg/kg through oral gavage and given daily for 3–4 weeks either alone or after the completion of chemotherapy in order to further reduce tumor cell burden.…”
Section: Control Of Cell Cycle Progression Prior To Immunotherapymentioning
confidence: 99%
“…Currently, high specific CDK4/6 inhibitors show a selective and potent therapeutic effect and fewer off-target toxicities than pan-CDK inhibitors for the treatment of breast cancer [14,15]. There are three CDK4/6 inhibitors which deactivate these CDK at <40 nM IC50 values: palbociclib, ribociclib and abemaciclib [16].…”
Section: Palbociclib Is the First Cell Cycle Inhibitor On Demonstratementioning
confidence: 99%
“…The phase 1 trials demonstrated safety, and phase 2 trials have shown single-agent activity with reversible neutropenia as the main toxic effect. The addition of palbociclib to endocrine therapy improves progression-free survival in naive endocrine therapy and resistant metastatic endocrine therapy [15]. The striking clinical activity exhibited by palbociclib in breast cancer announces its additional role in other cancer types.…”
Section: Palbociclib Is the First Cell Cycle Inhibitor On Demonstratementioning
confidence: 99%